2008
DOI: 10.1080/15313200802467908
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Resilience Factors of Bosnian Refugee Women Resettled in the Southern United States

Abstract: This study reports findings from a qualitative investigation of seven Bosnian refugee women's coping strategies as they resettled in two cities of the Southeastern United States over five years. It focuses on their personal experiences as refugees and the factors that contributed to their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 43 publications
5
93
1
Order By: Relevance
“…Five studies were conducted in HIC settings [38-40,45,46] and the other five in LMIC settings [41-44,47]. There was a wide variation in sample sizes, which ranged from 4 to 80.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted in HIC settings [38-40,45,46] and the other five in LMIC settings [41-44,47]. There was a wide variation in sample sizes, which ranged from 4 to 80.…”
Section: Resultsmentioning
confidence: 99%
“…In their review of resilience research among certain minority groups,McLaughlin et al (2009) identified two characteristics that they considered fundamental to resilience: heightened vulnerability and adaptation to risk. Resilience can determine the capacity to face safety-threatening events and still perform adequately (Charney, 2004) and it explains how a victim of violence can deal positively with past traumatic experiences (Lee et al, 2008; Sossou et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…The critical consciousness that developed in the current study's participants as reflected in their stories can be reinterpreted as resilience that may have tempered the impact of the traumatic events associated with the struggle for liberation. Resilience as described here, however, is more than a protective factor in postconflict coping (e.g., Schweitzer, Greenslade, & Kagee, 2007;Sossou, Craig, Ogren, & Schnak, 2008). Instead, resilience in this study exemplifies posttraumatic growth.…”
Section: Discussionmentioning
confidence: 77%